Hybrid optical-fibre/geopolymer sensors for structural health monitoring of concrete structures. (24th February 2015) - Perry, M; Saafi, M; Fusiek, G; Niewczas, P
Abstract: In this work, we demonstrate hybrid optical-fibre/geopolymer sensors for monitoring temperature, uniaxial strain and biaxial strain in concrete structures. The hybrid sensors detect these measurands via changes in geopolymer electrical impedance, and via optical wavelength measurements of embedded fibre Bragg gratings. Electrical and optical measurements were both facilitated by metal-coated optical fibres, which provided the hybrid sensors with a single, shared physical path for both voltage and wavelength signals. The embedded fibre sensors revealed that geopolymer specimens undergo 2.7 m ϵ of shrinkage after one week of curing at 42 °C. After curing, an axial 2 m ϵ compression of the uniaxial hybrid sensor led to impedance and wavelength shifts of 7 × 10 −2 and −2 × 10 −4 respectively. The typical strain resolution in the uniaxial sensor was 100 . The biaxial sensor was applied to the side of a concrete cylinder, which was then placed under 0.6 m ϵ of axial, compressive strain. Fractional shifts in impedance and wavelength, used to monitor axial and circumferential strain, were 3 × 10 −2 and 4 × 10 −5 respectively. The biaxial sensor's strain resolution was approximately 10 in both directions. Due to several design flaws, the uniaxial hybrid sensor was unable to accurately measure ambient temperature changes. The biaxial sensor, however, successfully monitored local temperature changes with 0.5 °C resolution.